Meteorological controls on evapotranspiration over a coastal salt marsh ecosystem under tidal influence - Huang, Ying; Guo, Haiqiang; Chen, Xuelong; Chen, Zihan; van der Tol, Christiaan; Zhou, Yunxuan; Tang, Jianwu (Agricultural and forest meteorology, 2019)
•PAR is a major control on ET in the coastal saltmarsh ecosystem at hourly, diel, and multiday scales.•The semidiurnal tides co-control ET with PAR, forming a complex ET pattern.•Wind direction fundamentally changed the nature of the interactions of ET with other variables.•Tidal inundation suppressed ET and changed its sensitivities to meteorological variables. Elucidating evapotranspiration (ET) patterns and drivers is of crucial importance for better understanding water and energy cycles. However, multiple controls on ET at coastal ecosystems that are subject to subdaily tidal flooding have not yet received attention. In this study, we investigated the response of ET to meteorological variables including photosynthetically active radiation (PAR), air temperature (Ta), vapour pressure deficit (VPD), and wind speed (WS) under semidiurnal tidal influence from hourly to seasonal timescales, on the basis of 3-year eddy-covariance (EC) measurements over a tidal salt marsh ecosystem of the Yangtze Delta. Our results show that, as with most terrestrial ecosystems, PAR is a major control on ET in this coastal salt marsh ecosystem at hourly, diel, and multiday timescales. However, the semidiurnal tides co-control ET with meteorological variables, forming a complex ET pattern at the hourly and subdaily scales. In the daytime, ET was primarily driven by PAR and VPD, whereas during the night, WS and friction velocity dominated the ET variability. We also found that wind direction fundamentally changed the nature of the interactions of ET with other variables. Moreover, tidal inundation suppressed ET and changed its sensitivities to PAR, Ta, VPD, and WS, a process that was especially obvious when offshore winds prevailed. The tidal flooding can affect ET directly through altering surface energy partitioning or plant metabolic activity, and indirectly through influencing meteorological conditions such as Ta and VPD. By explicitly considering the influence of tidal dynamics, this study revealed the significance in quantifying the ET contributions in coastal ecosystems to global water, carbon and energy cycles.